State of the art: Therapeutical strategies for the treatment of inflammatory bowel disease - Lautenschläger, Christian; Schmidt, Carsten; Fischer, Dagmar; Stallmach, Andreas (Current Drug Therapy, 2013)
Inflammatory bowel disease (IBD), commonly known as Crohn's disease and ulcerative colitis, is a frequently occurring disease in Gastroenterology, which is characterized by a chronic intestinal inflammatory ailment. The therapy of IBD is dominated by the administration of anti-inflammatory and immune-modulating drugs, which suppress the intestinal inflammation and thus improve disease-related symptoms. The enhanced insight and more detailed knowledge about the pathophysiological mechanisms of IBD accelerate the research and development of innovative drugs and new treatment strategies. In the last decades, many evolutionary as well as revolutionary innovations were developed and investigated in clinical trials. This review is believed to give an overview about established and future-orientated treatment approaches, including antisense gene therapy, non-embryonic stem cell therapy, leucocytapheresis and faecal biotherapy. Additionally, this review illuminates other smaller clinical trials, which follow interesting and maverick approaches, like lecithinmediated mucosal healing, Trichuris suis ova-supported treatment or several herbal treatment strategies. The main focus is pointed in the conceivable explanation of the respective molecular target mechanisms as well as potential to modulate the inflammatory and immunological process. Additionally, this review gives a brief insight in the therapeutical benefits and mediates about the risks of the respective treatment approaches. © 2013 Bentham Science Publishers.
CRIS-Team Scopus Importer:2020-10-13
Keywords: Anti-inflammatory therapy; Crohn's disease; Immune-modulating therapy; Inflammatory bowel disease; Mucosal healing; Ulcerative colitis